THE MINDSET-6 FRAMEWORK: A CURRICULUM BLUEPRINT FOR CULTIVATING INDUSTRY 6.0-READY ENTREPRENEURIAL MINDSETS IN MALAYSIAN UNDERGRADUATES - Zainuddin, Faizan Iza; Ismail, Farhana; Hussin, Siti Haslina (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Malaysia continues to grapple with a persistent misalignment between graduate capabilities and the rapidly evolving demands of the workforce, particularly in entrepreneurial readiness and digital adaptability. Although the Ministry of Higher Education reports graduate employability rates above 80%, many employers remain concerned about graduates’ limited creativity, risk appetite, and technological fluency. This paradox reveals a deeper structural issue: higher education institutions are producing academically competent yet entrepreneurially hesitant graduates. This critical review synthesizes empirical and conceptual studies published between 2019 and 2025 to identify key enablers, pedagogical innovations, and policy implications for cultivating an entrepreneurial mindset among Malaysian undergraduates. Findings suggest that attitude, perceived behavioural control, and ecosystem support are dominant predictors of entrepreneurial intention, while experiential, digital, and sustainability-oriented pedagogies strengthen mindset development. However, significant gaps persist, particularly in translating entrepreneurial intention into behaviour, integrating AI and data literacy, and embedding sustainability ethics into curricula. To address these limitations, this paper introduces the MINDSET-6 Framework, a curriculum blueprint encompassing Mindfulness and Ethics, Interdisciplinary AI and Data, Networked Learning, Design and Making, Sustainability, Entrepreneurial Finance, and Transversal 4Cs competencies. The framework positions entrepreneurship education not as a business module but as a transformative, human-centred process aligned with Malaysia’s transition toward a sustainable and digital Industry 6.0 economy.